Pengaruh PjBL Pada Materi Sistem Ekskresi Terhadap Hasil Belajar Dan Aktivitas Siswa - Amanda Savira; Ahmad Shafwan S Pulungan (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This study aims to evaluate the impact of the Project Based Learning model on learning outcomes and activities in the excretory system material among XI IPA SMA Negeri 2 Tanjung Morawa. This research employs a quantitative method with a true experimental approach. The research design used is a pretest-posttest control group design. The population of the study includes all XI IPA SMA Negeri 2 Tanjung Morawa, consisting of three classes. The research sample was selected using simple random sampling technique, resulting in XI IPA 2 as the experimental class and XI IPA 3 as the control class. The research results indicate a significant difference in students' learning outcomes, with the experimental class showing higher scores compared to the control class. The recapitulation of students' learning activities data reveals differences in learning activities between the two classes. The learning activities of students in the experimental class fall into the very high category, while the learning activities in the control class are in the high category.